ANALYSIS OF SLUG FLOW REGIME PREVENTION IN TWO-PHASE FLOW PIPES USING COMPUTATIONAL FLUID DYNAMICS - Shidqi Aiman Nandira, Muhammad
Multiphase flow is one of the phenomena in flow that is often encountered in many industrial and natural applications. As the name suggests, multi and phase, this flow involves two or more phases (liquid, gas, and solid). This phenomenon is important to study, especially in various industrial applications such as process industries, oil and gas, steam and geothermal power generation systems, and others. On a smaller scale, two-phase flow is one variation of multiphase flow that is often found in various industries and nature. The most common two-phase flow encountered is the liquid and gas phase. Slug flow, which is one of the regimes of two-phase flow, is considered detrimental and can cause damage to facilities, potentially reducing productivity in an industry. This flow is characterized by pressure and flow fluctuations. These fluctuations can cause damage to pipes. By using ANSYS Fluent software, an analysis of slug flow regime prevention was conducted. The simulation results show that slug flow in pipes has fluctuating pressure characteristics due to liquid buildup that can cover the pipe cross-section. The magnitude of the pressure is greatly influenced by the liquid phase accumulating in a cross-section. The simulation results of the designed solution show better mixing of the liquid and gas phases, so there is no liquid phase buildup, changing the flow regime to an annular flow regime. This results in better pressure distribution in the pipe cross-section and less high fluctuation. This is shown by a maximum pressure reduction from 11,079.05 Pa to 6,204.24 Pa, a decrease of 44.01%.